Belgium : Selected Issues. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper focuses on the fiscal challenge for Belgium in coping with population aging, including the sustainability of prevailing fiscal federalism arrangements across all levels of governments. The analysis demonstrates that the current strategy of upfront consolidation is likely to fall short of achieving sustainability. Further reductions in aging-related spending and growth and productivity-enhancing reforms beyond those assumed under the authorities' strategy appear to be necessary. The paper also assesses whether the wage bargaining framework, a key labor market institution, is conducive to preserving external competitiveness and raising employment rates.